Hydrothermal upgrading of biomass to biofuel; studies on some monosaccharide model compounds - Srokol, Zbigniew; Bouche, Anne-Gaëlle; van Estrik, Anton; Strik, Rob C.J; Maschmeyer, Thomas; Peters, Joop A (Carbohydrate research, 2004)
Reaction paths of the hydrothermal treatment of a 50 mM solution of glucose at 340 °C and 27.5 MPa for 25–204 s have been elucidated and are discussed in relation to the HTU process of biomass. During the hydrothermal upgrading of biomass, hydrolysis to glucose is an important step. To elucidate some of the reaction pathways that follow this initial hydrolysis, the hydrothermal treatment (340 °C, 27.5 MPa, 25–204 s) of dilute (50 mM) solutions of d-glucose and some other monosaccharides were studied. As a result of the increase of K w under subcritical conditions, both acid and base catalysed reactions occur. The acid catalysed reactions are mainly dehydrations leading initially to 5-hydroxymethylfurfural. Important base catalysed reactions result in glycolaldehyde and glyceraldehyde. Further fragmentations and dehydrations lead to a variety of low molecular weight compounds such as formic acid, acetic acid, lactic acid, acrylic acid, 2-furaldehyde and 1,2,4-benzenetriol. Important pathways leading to a decrease of the O-content of the liquid reaction products start from the intermediate glyceraldehyde, which forms pyruvaldehyde, which in its turn is converted into formic acid and acetaldehyde. The latter compound can also be formed via isomerisation of glyceraldehyde into lactic acid followed by decarbonylation.